Simulating the transport and chemical evolution of biomass burning pollutants originating from Southeast Asia during 7-SEAS/2010 Dongsha experiment. (July 2015) - Chuang, Ming-Tung; Fu, Joshua S.; Lin, Neng-Huei; Lee, Chung-Te; Gao, Yang; Wang, Sheng-Hsiang; Sheu, Guey-Rong; Hsiao, Ta-Chih; Wang, Jia-Lin; Yen, Ming-Cheng; Lin, Tang-Huang; Thongboonchoo, Narisara; et al.
Abstract: This study aimed to simulate the transport of biomass burning (BB) aerosol originating from Southeast Asia (SEA) during the Dongsha Experiment conducted from March 2010 to April 2010. Transport pathways were reanalyzed and steering flow in the mid-latitude areas and anticyclones in low-latitude areas were found to control the transport of BB plume after it was injected to a high atmosphere. For the 12 simulated and observed events at Mt. Lulin (2862 m MSL; 23°28′07″ N, 120°52′25″ E), the 72 h backward trajectories were all tracked back to southern China and northern Indochina, which were the locations of the largest BB fire activities in SEA. Chemical evolutions of BB pollutants along the moving trajectories showed that organic matter was always the dominant component in PM2.5, consistent with the observations at both near-source regions and Mt. Lulin. For nitrogen species, nearly all NO x molecules oxidized into HNO3, NO3 −, PAN, and PANX in fires or near fires. The synchronic consumption of NO x, SO2, and NH3 explained the production of the major components of inorganic salts. In the moving BB plume, sulfate concentration increased with decreased nitrate concentration. Ratios of ammonium to PM2.5 and elemental carbon to PM2.5 remained nearly constant because additional sources were lacking. Highlights: Reanalysis of transport of biomass burning plume originating from SEA. Chemical evolution of biomass burning pollutants during long-range transport. Combine WRF/HYSPLIT/CMAQ to analyze the compositions of biomass burning plume.